2019
DOI: 10.1111/ecog.04492
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and biotic drivers of soil microbial β‐diversity across spatial and phylogenetic scales

Abstract: Soil microbial communities play a key role in ecosystem functioning but still little is known about the processes that determine their turnover (β-diversity) along ecological gradients. Here, we characterize soil microbial β-diversity at two spatial scales and at multiple phylogenetic grains to ask how archaeal, bacterial and fungal communities are shaped by abiotic processes and biotic interactions with plants. We characterized microbial and plant communities using DNA metabarcoding of soil samples distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 88 publications
4
21
0
Order By: Relevance
“…This confirmed that landscape descriptors provide valuable complementary information to local abiotic conditions (hypothesis 1). The opposite trend was observed for smaller buffers, highlighting the importance of scale in microbial landscape ecology (Cadotte, 2006;Chalmandrier et al, 2019;Lembrechts et al, 2020) as reported for macro-organisms (Bradter et al, 2013;McGill, 2010). In agreement with hypothesis 2, soil protist diversity was more sensitive to landscape composition (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…This confirmed that landscape descriptors provide valuable complementary information to local abiotic conditions (hypothesis 1). The opposite trend was observed for smaller buffers, highlighting the importance of scale in microbial landscape ecology (Cadotte, 2006;Chalmandrier et al, 2019;Lembrechts et al, 2020) as reported for macro-organisms (Bradter et al, 2013;McGill, 2010). In agreement with hypothesis 2, soil protist diversity was more sensitive to landscape composition (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…The ITS region is not amenable to robust multiple alignments and phylogenetic reconstruction much beyond the genus level. Therefore, phylogenetic measures require inferring phylogenetic distance matrices that may rely on ultrametric trees of conserved gene(s) (Davison et al, 2015; Horn et al, 2014), grafting phylogenies (Fouquier et al, 2016) or mapping of OTUs to distance‐weighted phylogenies (Perez‐Izquierdo et al, 2019) or hierarchical taxonomic trees (Chalmandrier et al, 2019; Tedersoo, Sánchez‐Ramírez, et al, 2018). We recommend analysis of the ITS region and flanking, phylogenetically informative 18S or 28S rRNA genes for species‐level identification and phylogenetic placement, respectively.…”
Section: Statistical Data Analysesmentioning
confidence: 99%
“…Shifts in phylogenetic diversity can be studied using standardised phylogenetic diversity (PD; averaged unique branch length), mean phylogenetic distance (MPD), UniFrac distance and mean nearest taxon distance (MNTD), the latter emphasising genus‐level similarities. Testing phylogenetic conservatism, overdispersion and turnover across phylogenetic scales (Tucker et al, 2017) may be informative in analyses of plant‐fungal interactions (Chalmandrier et al, 2019), fungal community assembly processes (Roy et al, 2019) and phylogeographic patterns (Turon et al, 2020). These measures and similar indices for community turnover can be calculated in phylocom (Webb et al, 2008), the R packages picante (Kembel et al, 2010), S.phylomaker (Qian & Jin, 2016) and PhyloMeasures (Tsirogiannis & Sandel, 2016) as well as other open‐access scripts (Chalmandrier et al, 2019).…”
Section: Statistical Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…productivity or fertility) gradient, but findings may not generalize across multiple individual gradients (Alzarhani et al 2019). Indeed, several studies have indicated that the drivers of microbial community composition may strongly vary with spatial and/or environmental contexts (Martiny et al 2011;Shi et al 2018;Chalmandrier et al 2019) and that predictability of the soil microbiome depends on spatial scale (Averill et al 2021).…”
Section: Introductionmentioning
confidence: 99%